2008
DOI: 10.1111/j.1462-5822.2008.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of type IV secretion inHelicobacter pyloripathogenesis

Abstract: SummaryHelicobacter pylori is a highly successful humanspecific gastric pathogen that colonizes more than half the world's population. Infection with this bacterium can induce gastric pathologies ranging from chronic gastritis to peptic ulcers and even cancer. Virulent H. pylori isolates harbour the cag (cytotoxin-associated genes) pathogenicity island, a 40 kb stretch of DNA that encodes components of a type IV secretion system (T4SS). This T4SS forms a pilus for the injection of virulence factors into host t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
222
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 228 publications
(229 citation statements)
references
References 83 publications
(127 reference statements)
3
222
0
4
Order By: Relevance
“…One candidate is H. pylori peptidoglycan, which is translocated into host cells by the cag type IV secretion system and sensed by intracellular Nod1, which then activates NF-B-dependent responses such as secretion of interleukin-8 and ␤-defensin 2 (Viala et al, 2004;Boughan et al, 2006). Another possibility based on a recent investigation (Kwok et al, 2007) is that binding of CagL to cell surface ␣ 5 ␤ 1 integrins can alter local membrane dynamics and eventuate in the assembly of focal adhesions that trigger integrin signaling cascades (Backert and Selbach, 2008), which may aberrantly activate p120.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One candidate is H. pylori peptidoglycan, which is translocated into host cells by the cag type IV secretion system and sensed by intracellular Nod1, which then activates NF-B-dependent responses such as secretion of interleukin-8 and ␤-defensin 2 (Viala et al, 2004;Boughan et al, 2006). Another possibility based on a recent investigation (Kwok et al, 2007) is that binding of CagL to cell surface ␣ 5 ␤ 1 integrins can alter local membrane dynamics and eventuate in the assembly of focal adhesions that trigger integrin signaling cascades (Backert and Selbach, 2008), which may aberrantly activate p120.…”
Section: Discussionmentioning
confidence: 99%
“…dependent delivery of CagA and other cag island substrates from the bacterial cytoplasm directly into host cells (Backert and Selbach, 2008). Inactivation of cagE, therefore, results in a nonfunctional type IV cag secretion system.…”
Section: Molecular Biology Of the Cell 4112mentioning
confidence: 99%
See 1 more Smart Citation
“…Adherent of bacterium to gastric epithelial cells is critical to initiate the gastric inflammatory response with different clinical outcomes in humans (Hessey et al, 1990;Logan, 1996;Segal et al, 1996;Rieder et al, 1997). CagL (a VirB5 ortholog) is a bacterial factor that is known as a pilus protein Backert and Selbach, 2008;Backert et al, 2011), Integrin α5β1 is a receptor on gastric epithelial cell that CagL binds to; by its arginineglycine-aspartate (RGD) motif, this interaction activates α5β1 receptor and facilitates the delivery of CagA oncoprotein through type 4 secretion system (T4SS) into the epithelial cell (Parsonnet et al, 1997;Kwok et al, 2007;Backert and Selbach, 2008;Backert et al, 2011;Shaffer et al, 2011). CagL is associated with two other cag PAI proteins; CagI and CagH.…”
Section: Genotypes Predict Risk Of Peptic Ulcerations But Not Gastricmentioning
confidence: 99%
“…The only reported effector protein translocated into the host cell by the cag-PAI T4SS is CagA [28]. Therefore, CagA has been recognized as a genetic marker for the cagPAI locus [29] and H. pylori-associated disease development [1,2]. Sequence comparison of the cagPAI genes of more than 30 H. pylori isolates have shown that the gene order and content are highly conserved [30].…”
Section: General Role Of Type IV Secretion Systems (T4sss) In Dna Excmentioning
confidence: 99%